Management of primary molars with irreversible pulpitis employing tampon pulpotomy: Report of three cases with 34‐month mean follow‐up - Saeed Asgary; Alireza Sarraf Shirazi; Sedigheh Sabbagh (Clinical Case Reports, 2021)
Abstract This study suggests that tampon‐based coronal pulpotomy using a calcium silicate–based biomaterial can be a reliable approach for the treatment of vital primary molars with irreversible pulpitis.